2019
DOI: 10.1094/mpmi-07-18-0203-r
|View full text |Cite
|
Sign up to set email alerts
|

Disruption and Overexpression of the Gene Encoding ACC (1-Aminocyclopropane-1-Carboxylic Acid) Deaminase in Soil-Borne Fungal Pathogen Verticillium dahliae Revealed the Role of ACC as a Potential Regulator of Virulence and Plant Defense

Abstract: It has been suggested that some microorganisms, including plant growth–promoting rhizobacteria, manipulate the level of ethylene in plants by degrading 1-aminocyclopropane-1-carboxylic acid (ACC), an ethylene precursor, into α-ketobutyrate and ammonia, using ACC deaminase (ACCd). Here, we investigated whether ACCd of Verticillium dahliae, a soil-borne fungal pathogen of many important crops, is involved in causing vascular wilt disease. Overexpression of the V. dahliae gene encoding this enzyme, labeled as ACC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 75 publications
1
34
0
Order By: Relevance
“…Pathogenic microbes can employ similar strategies with beneficial microbes to colonize their hosts. For example, overexpression of ACC deaminase gene in V. dahliae significantly lowered ACC levels in the roots of infected tomato plants and increased both its virulence and the fungal biomass in the vascular tissues of plants (Tsolakidou et al, 2019b). Therefore, future studies need to address how functions shared by both beneficial and pathogenic microbes are perceived by the plants and how plants can maintain a balance in the rhizosphere.…”
Section: Rhizosphere Microbiome As a Source Of Benefits For The Plantmentioning
confidence: 99%
“…Pathogenic microbes can employ similar strategies with beneficial microbes to colonize their hosts. For example, overexpression of ACC deaminase gene in V. dahliae significantly lowered ACC levels in the roots of infected tomato plants and increased both its virulence and the fungal biomass in the vascular tissues of plants (Tsolakidou et al, 2019b). Therefore, future studies need to address how functions shared by both beneficial and pathogenic microbes are perceived by the plants and how plants can maintain a balance in the rhizosphere.…”
Section: Rhizosphere Microbiome As a Source Of Benefits For The Plantmentioning
confidence: 99%
“…ACC is required for the division of the guard mother cell (GMC) likely via the regulation of the indicated cell cycle regulators (Shin et al, 2014). (C) Overexpression of the ACC deaminase from the fungal pathogen of tomato, Verticillium dahliae, enhances its virulence, and pre-treatment of tomato plants with ACC reduced the symptoms of V. dahliae infection even in ethylene-insensitive mutants (Tsolakidou et al, 2019). (D) ACC is involved in cell wall signaling regulating anisotropic elongation of root cells (Xu et al, 2008;Tsang et al, 2011).…”
Section: Acc In Plant Development and Beyondmentioning
confidence: 99%
“…The fungal pathogen, Verticillium dahliae is a soil-borne pathogen of many plant species, causing vascular wilt disease. Tsolakidou et al (2019) found that genetic modulation of ACC levels in V. dahliae affected its microsclerotia development and hyphae growth. Overexpression of ACC deaminase in V. dahliae led to increased virulence on tomato and eggplant, including enhanced wilting and greater fungal growth.…”
Section: Polko and Kiebermentioning
confidence: 99%
“…Tomato lines with a mutation in this receptor present an impaired ethylene perception, due to a single amino acid change in the ethylene-binding domain (Pro36Leu) [19][20][21]. These mutants, named Never ripe (Nr), have been used to study the relationship between ethylene signaling and disease development in different pathogens [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%